Recombinant expression of surfactant protein H (SFTA3) in Escherichia coli - Schröder, Henrik; Sollfrank, L.; Paulsen, Friedrich; Bräuer, Lars; Schicht, Martin (Annals of Anatomy-Anatomischer Anzeiger, 2016)
Surfactant proteins are broadly understood to be an important structural and functional part of the lung surfactant system. These proteins influence the intra-alveolar surface tension and contribute to innate immunity of the lung. Beside the four already known surfactant proteins SP-A, SP-B, SP-C and SP-D, two novel SPs (SP-G/SFTA2 and SP-H/SFTA3) have recently been described. These show no sequential or structural similarity with the already known SPs. However, bioinformatic prediction tools suggest physicochemical properties, which have already been described for other surfactant proteins. Although it is known that SFTA2 and SFTA3 are expressed in different human tissues, their distinct functional properties remain unclear. Here, we describe the establishment of a stable expression system for recombinant SFTA3 protein synthesis in Escherichia coli. This gives rise to future experiments with the overall aim to further examine and characterize this novel protein in more detail.
EVALuna2:34493